The Effect of Hypoallergenic Diagnostic Diet in Adolescents and Adult Patients Suffering from Atopic Dermatitis - Jarmila Celakovská; K Ettlerová; K Ettler; J Bukac; M Belobrádek (Wolters Kluwer Medknow Publications, 2012)
Aim: To evaluate the effect of a diagnostic hypoallergenic diet on the severity of atopic dermatitis in patients over 14 years of age. Materials and Methods: The diagnostic hypoallergenic diet was recommended to patients suffering from atopic dermatitis for a period of 3 weeks. The severity of atopic dermatitis was evaluated at the beginning and at the end of this diet (SCORAD I, SCORAD II) and the difference in the SCORAD over this period was statistically evaluated. Results: One hundred and forty-nine patients suffering from atopic dermatitis were included in the study: 108 women and 41 men. The average age of the subjects was 26.03 (SD: 9.6 years), with the ages ranging from a minimum of 14 years to a maximum of 63 years. The mean SCORAD at the beginning of the study (SCORAD I) was 32.9 points (SD: 14.1) and the mean SCORAD at the end of the diet (SCORAD II) was 25.2 points (SD: 9.99). The difference between SCORAD I and SCORAD II was evaluated with the Wilcoxon signed-rank test. The average decrease of SCORAD was 7.7 points, which was statistically significant (P=.00000). Conclusion: Introduction of the diagnostic hypoallergenic diet may serve as a temporary medical solution" in patients suffering from moderate or severe forms of atopic dermatitis. It is recommended that this diet be used in the diagnostic workup of food allergy.